FEED NUTRITIONAL VALUE OF ENRICHED CYCLOPOID COPEPODS (Oithona sp.) AS A POTENTIAL LIVE FEED IN LARVAL REARING OF THE MUD CRAB (Scylla olivacea) - Wan Nur Amirah Binti Wan Yuslan (Universiti Malaysia Terengganu, 2022)
The copepod Oithona sp. can be used as a natural feed in rearing larvae of the mud crab Syclla olivacea. However, copepod is not readily obtainable due to their characteristics as seasonal zooplankton, causing limitation of using copepods. Different dietary additives for Oithona sp. such as swiftlet waste, soybean meal, rice bran, and Nannochloropsis sp. were compared. The objectives of this study were to analyse the growth and productivity (hatching time, hatching rate, generation time, lifespan, spawning and, offspring production) of Oithona sp. in different dietary enrichment, to compare the protein, lipid and fatty acid analysis of enriched Oithona sp., unenriched with Artemia, and to evaluate the nutrient transfer of enriched Oithona sp. in improving the growth development and survival of early -stage mud crab (Scylla olivacea). The effects of different feeding regimes on the survival and development of S. olivacea larvae were studied in two phases of the crab larval development: Phase 1 (zoea 1 to zoea 2 stage) and Phase 2 (zoea 5 to megalopa stage). The feeding regimes were T1: Oithona sp. enriched with rice bran, T2: Oithona sp. enriched with Nannochloropsis sp., T3: Oithona sp. enriched with a mixture of rice bran and Nannochloropsis sp., and T4: Artemia. The results showed that rice bran and Nannochloropsis sp. additives produced the best outcomes in terms of specific growth rate (0.109 ± 0.002 day -1 and 0.104 ± 0.001 day -1 ) of Oithona sp., protein content (66.83 ± 2.25% and 72.08 ± 2.02%), and lipid content (21.98 ± 1.41% and 18.09 ± 1.18%) respectively. A mixture of rice bran and Nannochloropsis sp. (41.62%) as dietary additives also improved the polyunsaturated fatty acids (PUFAs) content of Oithona sp. as compared with mono diet applied such as rice bran (28.16%) and Nannochloropsis sp. (31.35%). The average survival rate of S. olivacea from zoea 1 until megalopa shows that, T3 (20.20 ± 1.97%) was higher than T1 (13.87 ± 0.90%), T2 (12.47 ± 1.14%) or T4 (3.13 ± 1.29%). In conclusion, improving the survival rate of crab larvae in commercial hatcheries by using precise early-stage foods is fundamental to enhance seed production technology of mud crabs.